2022
DOI: 10.1111/ijag.16597
|View full text |Cite
|
Sign up to set email alerts
|

Design of mechanically advantaged glasses with hydration‐induced stress profiles

Abstract: The glass composition design work leading to the discovery of highly crack resistant glasses exhibiting hydration‐induced stress profiles is described. Initial hydration studies on ternary aluminosilicate glasses show the importance of potassium for facilitating hydration. Further modification of the glass composition through the incorporation of P2O5 increased the hydration rate such that a specimen with a 29‐µm hydration depth was prepared by holding in an 85°C 85% relative humidity chamber for 65 days. Not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…As H 2 O (and H 3 O + ) is larger than Na + this results in an apparent densification of the network detected by the drop in S . These results provide the first clear observation of a reduction of the free volume on the glass surface during HT and are consistent with the build‐up of compressive residual stresses, already spotted in previous works, 27,30,40 that can partially explain the water‐induced toughening (Figure 1).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As H 2 O (and H 3 O + ) is larger than Na + this results in an apparent densification of the network detected by the drop in S . These results provide the first clear observation of a reduction of the free volume on the glass surface during HT and are consistent with the build‐up of compressive residual stresses, already spotted in previous works, 27,30,40 that can partially explain the water‐induced toughening (Figure 1).…”
Section: Discussionsupporting
confidence: 91%
“…A few papers appeared describing the effect of hydrothermal treatments (HT) on increasing the glass resistance on flaw formation after Vickers indentation. 25,26 In the case of specifically designed glasses subjected to HT, the critical load can be as high as 20 kgf 27 (about two orders of magnitude larger than normal SLS). These studies confirmed that the hydrated glass surfaces are more resistant to crack formation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it was shown that H 2 O vapor treatments can be used to modify the surface mechanics of various silicate glasses in very short treatment times [29]. Similar to IOX, the incorporation of water into the glass surface is thought to enable the generation of persistent layers of compressive stress [30], [31], while also affecting material plasticity, elastic properties and fracture characteristics [32], [33].…”
Section: Introductionmentioning
confidence: 99%